DRIVING FORCES: EXPLORING THE IMPACT OF SOCIAL MOTIVES ON ENTREPRENEURIAL ORIENTATION AND KNOWLEDGE MANAGEMENT BEHAVIOR THROUGH THE MEDIATING LENS OF ENTREPRENEURIAL ORIENTATION - Hadipoespito, Randy; Herlina, Maria Grace; Ikhsan , Ridho Bramulya (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
This study explores the impact of McClelland's social motives on entrepreneurial orientation (EO) and knowledge management behaviour (KMB), examining EO's mediating role in this relationship. Utilising a sample of 302 employees from Greater Jakarta, data were collected through online surveys and analysed using partial least square structural equation modeling (PLS-SEM). The findings reveal that social motives significantly influence EO, positively impacting KMB. The study underscores the importance of fostering a workplace culture that supports social motives such as achievement, power, and affiliation, as these drive entrepreneurial behaviours and effective knowledge management practices. EO serves as a crucial mediator, amplifying the beneficial effects of social motives on KMB. These insights suggest that organisations can enhance their innovation and competitive advantage by strategically managing human and knowledge resources. Practical implications include implementing policies and training programs that cultivate social motives and entrepreneurial orientation. Future research should explore the longitudinal effects and the moderating roles of organisational culture and leadership style, providing a more comprehensive understanding of these dynamics across diverse contexts.